Judicial Protection of Civil Rights in Ukraine: National Experience through the Prism of European Standards - BORYSOVA, Valentyna I.; IVANOVA, Kseniia Yu.; IUREVYCH, Iryna V.; OVCHARENKO, Olena M. (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019DO - 10.14505//jarle.v10.1(39).09, 2019)
The relevance of the academic study of the problems of judicial protection of civil rights is conditioned by the ongoing judicial reform in Ukraine, which has identified new priorities in this area, since in 2016, the legislator provided the Supreme Court and the Constitutional Court with effective instruments for the protection and restoration of violated or unrecognized rights. The purpose of this study is to systematically examine the organizational and procedural aspects of the Institute for the Judicial Protection of Subjective Civil Rights and the Law of Interest in Ukraine, to determine the content of this institution and its development trends based on the results of the 2016 judicial reform. To achieve this purpose, both methods of doctrinal analysis (systemic, structural, functional, hermeneutic) and tools of empirical research (statistical, method of critical analysis of judicial precedents) were applied. As a result, the author's original vision of the issue of judicial protection of subjective civil rights and interests protected by law has been formulated.